Resection and anastomosis in one stage in acute complications of colon cancer - Asiner, Boris; Rodriguez de Vecchi, Victoriano; Valls, Alberto; Balboa, Oscar (Cirugía del Uruguay, 1971)
Seven acute colon carcinoma complications are presented. Resection and anastomosis were made without deads or éinastomotics faillures. In patients with peritoneal complication this technique is to be considered especially in right and even transverse localization. It can also be considered in left obstructive carcinoma with incompetent ileo-cecal valve and as alternative procedure in patients with good general and local conditions with complete obstruction of the colon of the closed-loop type. A correct and medium clinical balance needed in all cases taking into account the posibilities of the equipment.